The Impact of Beauty Bloggers’ Online Review towards Shopping Tour Interest of Cosmetic Products in Jakarta - Fitriana, Rina; Amrullah, Amrullah; Suryani, Intan (Institut Pariwisata Trisakti, 2020)
This study is aimed at finding out the impacts of beauty bloggers’ online review in encouraging women’ interest to carry on shopping tours on cosmetic products in Jakarta. The study uses descriptive method by administering a questionnaire to 100 women respondents who carry on shopping tours on cosmetic products in Jakarta. The findings show that that beauty bloggers’ online review possesses a strong relationship as many as 0,682 towards the shopping tour interest of cosmetic products in Jakarta which as many as 46,5%. Beauty bloggers share information and recommendations based on their own experiences by using blog with the contents in the forms of captions, photos, and videos about a certain cosmetic product so that it encourages shopping tours on cosmetic products. Therefore, in the present study, H0 is rejected and H1 is accepted, in which t count is 9,235 > t table 1,984. Thus, it can be concluded that the impacts of beauty blogger’ online review towards the shopping tour interest on cosmetic product in Jakarta indeed existed.